Kepemimpinan Transformasional Karakter Hughie Campbell Dalam Film The Boys - Ramadhan, Dani (DIGICOM : Jurnal Komunikasi dan Media, 2024)
Leadership is an essential element in every organization, including the one featured in the movie.This research aims to analyze the character of Hughie Campbell in the The Boys series through theperspective of transformational leadership. The purpose of this research is to show the character ofHughie, despite not having superpowers, able to display strong leadership characteristics andinfluence his peers. This research uses a case study approach and descriptive method to delve deeperinto the transformational leadership characteristics possessed by Hughie, such as idealizedinfluence, inspirational motivation, intellectual stimulation, and individualized consideration. Theresults showed that Hughie was able to influence his colleagues through strong moral principles,providing inspiration in difficult situations, and encouraging his team to think critically andencouraged his team to think critically in the face of challenges. In addition, he also paid attentionto the well-being of individuals in the team, which created a closer working relationship. closerworking relationships. This study concludes that transformational leadership theory is relevant toanalyze in a fictional context and has real implications in understanding leadership in the realworld.